2016
DOI: 10.1590/1413-81232015214.10472015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome, insulin resistance and other cardiovascular risk factors in university students

Abstract: Metabolic syndrome, insulin resistance and other cardiovascular risk factors in university studentsSíndrome metabólica, resistência insulínica e outros fatores de risco cardiovascular em universitários

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 22 publications
2
20
0
6
Order By: Relevance
“…It has also been shown in the HELENA study that muscular and cardiorespiratory fitness are independently associated 34. Results from the present study support the conclusions from the studies by Dalleck,25 Barbosa,5 and the HELENA study34 that CVD may increase in the future, and that there is need for early prevention aiming to increase both muscle strength and aerobic fitness in young subjects to prevent CVD. If aerobic capacity is regained, it may have a beneficial effect on cardiometabolic health in the future 35…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It has also been shown in the HELENA study that muscular and cardiorespiratory fitness are independently associated 34. Results from the present study support the conclusions from the studies by Dalleck,25 Barbosa,5 and the HELENA study34 that CVD may increase in the future, and that there is need for early prevention aiming to increase both muscle strength and aerobic fitness in young subjects to prevent CVD. If aerobic capacity is regained, it may have a beneficial effect on cardiometabolic health in the future 35…”
Section: Discussionsupporting
confidence: 88%
“…They found that 21% of the students were insulin resistant and that as many as 61% had low HDL-C 5. A problem with this type of studies is that there are several definitions of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En lo que concierne a las diferencias entre hombres y mujeres, encontramos un patrón donde los hombres tuvieron mayores prevalencias del SM y de algunos de sus componentes como la hiperglucemia, la hipertensión arterial y el HDL-C bajo, particularmente en México, Canadá, Colombia y EUA. Otros autores también han reportado que los hombres tienen mayor prevalencia del SM que las mujeres 45 . Además, las adolescentes tienen mayores niveles de insulina que los varones 46 .…”
Section: Resultsunclassified
“…Ésto podría ser útil para el control de la glucemia, aunque puede favorecer la resistencia a la insulina. Si bien las mujeres jóvenes suelen ser más sedentarias que los hombres, estos últimos fuman e ingieren más alcohol lo que favorece la presencia de alteraciones metabólicas 45 .…”
Section: Resultsunclassified